Impact of gold mining on physico-chemical water quality of sokor river located in Sokor forest reserve, Tanah Merah, Kelantan - Wong, Hie Ling (2012)
Gold mining is the processes and techniques to remove the gold from the ground either through surface mining or underground mining. The improper gold mining practices in extraction, transportation, and purification over the years might affect the stuctures and functions of the ecological systems in maintaining a healthy and resilience enviromental. In this study, the impact of gold mining activities were analyzed for the physico-chemical water quality of sokor River that was located within the Permanent Forest Reserve Sokor.